Insects an alternative for sustainable production in Mexico (Agro Productividad, 2022)
Objective: To analyze the sociocultural, economic and environmental aspects of insects in Mexico. Design/methodology/approach: From October 2021 to January 2022, a bibliographic review was carried out searching for literature available in Google academic, Sciencedirect, SpringerLink, Google patent, EBSCO, Semantic Scholar databases and content available through remote access from CONRICyT. The bibliographic systematization of the consulted articles was developed from the Excel 2016 program and the Mendeley Desktop software, version 1.19.4.Results: Entomology has a high ecological, economic and social value, directed towards the horizons of food security, care for the environment and as an alternative for productive diversification. The economic importance of edible insects for Mexico was highlighted, visualizing commercial alternatives to small producers.Limitations/implications: The results only present data referring to Mexico, it is recommended to expand the search effort to know the current state of this topic worldwide.Findings/Conclusions: It was possible to demonstrate the importance of sustainability that insects present in Mexico. Awareness practices are suggested to mitigate neophobia and strengthen the adoption and consumption of this resource in the different social strata of Mexican society.